Pilot proteomic study of locally advanced rectal cancer before and after neoadjuvant chemoradiotherapy indicates high metabolic activity in non‐responders' tumor tissue. Issue 1 (7th September 2022) - Babic, Tamara; Lygirou, Vasiliki; Rosic, Jovana; Miladinov, Marko; Rom, Aleksandra Djikic; Baira, Eirini; Stroggilos, Rafael; Pappa, Eftychia; Zoidakis, Jerome; Krivokapic, Zoran; Nikolic, Aleksandra
Abstract: Purpose: In the search for candidate predictive biomarkers to evaluate response to neoadjuvant chemoradiotherapy (nCRT) in rectal cancer, only a few studies report proteomic profiles of tumor tissue before and after nCRT. The aim of our study was to determine differentially expressed proteins between responders and non‐responders before and after the therapy in order to identify candidate molecules for prediction and follow‐up of response to nCRT. Experimental Design: The study has included tissue sections of rectal tumor and non‐tumor mucosa from five responders and five non‐responders taken before and after nCRT from patients with locally advanced rectal cancer. Extracted proteins were analyzed by LC‐MS/MS analysis followed by a set of bioinformatics analyses. Result: Proteomics analysis provided a mean of approximately 1050 protein identifications per sample. A comparison of proteomic profiles between responders and non‐responders has identified 18 differentially expressed proteins. Pathway analysis demonstrated high metabolic activity in non‐responders' tumors before nCRT, indicating the presence of intrinsic chemoradioresistance in these subjects. Two proteins associated with poor prognosis in colorectal cancer, ADAM10 and CAD, were identified as candidate predictive biomarkers as they were present in non‐responders only. Conclusions and Clinical Relevance: Shortlisted proteins from our study should be further validated as candidate biomarkers for response to routinely applied nCRT protocols.